Managing calcaneal fractures through modified sinus tarsi approach and headless screws fixation (Indian Journal of Case Reports, 2024)
The calcaneus is the most commonly fractured tarsal bone, and the treatment of patients with intraarticular calcaneal fractures remains controversial. Operative treatment utilizing extensile approaches provides excellent exposure of the fracture but is associated with high rates of wound complications. This case report discusses the application of the mini-open reduction technique through the modified sinus tarsi approach and fixation with headless cannulated screws for the reconstruction of an intra-articular tongue-type calcaneus fracture in a 67-year-old male patient who presented with a history of falling from a 2-meter height, sustained a dislocated intra-articular calcaneal fracture. Using a 2–3 cm lateral transverse incision, we reduced the fracture and percutaneously fixed it with two headless cannulated screws. The patient fully regained his activity level by the 3rd-month postoperatively. At the 9-month follow-up, foot and ankle functions were found to be satisfactory. Minimally invasive treatment of calcaneal fractures achieved through the modified sinus tarsi approach provides excellent fracture exposure and percutaneous fixation using headless cannulated screws ensures better outcomes.